Analysis of distance between goalkeeper and less advanced team mate in spanish first division football games - Fradua, L.; Zubillaga, L.; Ruiz-Ruiz, C.; Caro, O.; Fernandez-Garcia, A. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Match analysis can be used to organize and design specific exercises (Sainz De Baranda, Ortega & Palao, 2008). In football, the distance between goalkeeper and his less advanced team matte is important because attackers use to score after making runs to this space and receive the ball in front of the goal. Therefore it should be considered for training practice. The aim of this study was to analyze the distance between goalkeeper and his less advanced team matte depending on the position of the ball on the pitch in football matches. Methods The AMISCO® system was used to register the distance between the defending goalkeeper and his less advanced team matte in four Spanish First Division matches of the season 2007-08. A total of 2568 data were collected. Pitch zone was the independent variable (see figure 1). A one-way ANOVA was performed. Results & Discussion Figure 1 shows the distances between the defending goalkeeper and his less advanced team matte that coaches should implement in training exercises to simulate spatial-temporal constraints similar to competition. Different distances might be applied depending on the position of the pitch where the trained technical-tactical skill uses to take place. Conclusion Distances between defending goalkeeper and his less advanced team matte decreased from 33,07 7,65 to 12,54 7,81 meters as the ball was nearer to their goal in football matches.